Pengaruh Good Corporate Governance terhadap Pengungkapan Sustainability Report dengan Ukuran Perusahaan sebagai Pemoderasi - Multy Adra Madona (Jurnal Optimasi Sistem Industri, 2020)
The purpose of this study is to determine and analyze the effect of the proportion of independent commissioners, audit committees, and managerial ownership on sustainability report disclosures with firm size as a moderating variable. The research population is mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 as many as 41 companies, 8 companies do not meet the criteria. The sampling technique used purposive sampling to produce 99 samples and analysis units. The data analysis tool used is logistic regression analysis and MRA using the IBM SPSS 23.0 software. The results showed that the proportion of independent commissioners had a significant negative effect on sustainability report disclosure, while the audit committee and managerial ownership did not affect the disclosure of sustainability report. The proportion of independent commissioners moderated by firm size showed positive results that strengthened the influence of sustainability report disclosures. In addition, audit committees and managerial ownership that are moderated by firm size did not the effect of disclosure of sustainability reports. The suggestion for future research is to pay attention to the extent of disclosure and quality of the sustainability report content by looking at disclosure indicators in accordance with the Global Reporting Initiative guidelines.